2022
DOI: 10.1002/job.2668
|View full text |Cite
|
Sign up to set email alerts
|

Do moral disengagers experience guilt following workplace misconduct? Consequences for emotional exhaustion and task performance

Abstract: Summary According to Bandura, moral disengagement facilitates misconduct by minimizing feelings of guilt that normally arise when one contemplates wrongdoing. While trait moral disengagement has been negatively associated with anticipatory guilt, scholars have yet to fully consider its impact on guilt post‐misconduct. In this paper, we examine the indirect effects of trait moral disengagement on post‐misconduct guilt, and downstream effects on employees' mental health and performance. Lastly, we explore the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…Moreover, moral identity symbolisation has been associated with motivating prosocial behaviour through recognition and internalisation processes, suggesting that recognising and internalising moral identity can encourage individuals to engage in altruistic actions (Winterich et al 2013). On the other hand, moral disengagement has been linked to guilt following unethical behaviours, indicating a potential emotional toll on individuals who exhibit moral disengagement tendencies (Ogunfowora et al 2022). In conclusion, the synthesis of these studies emphasises the importance of understanding the interplay between religious commitment, moral identity, moral disengagement, and social behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, moral identity symbolisation has been associated with motivating prosocial behaviour through recognition and internalisation processes, suggesting that recognising and internalising moral identity can encourage individuals to engage in altruistic actions (Winterich et al 2013). On the other hand, moral disengagement has been linked to guilt following unethical behaviours, indicating a potential emotional toll on individuals who exhibit moral disengagement tendencies (Ogunfowora et al 2022). In conclusion, the synthesis of these studies emphasises the importance of understanding the interplay between religious commitment, moral identity, moral disengagement, and social behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent literature (Antonetti et al, 2018 ; Kemp, 2023 ), the delayed effects of guilt appeals were found to be lower across all studies. Considering the transient nature of guilty feelings after misdeed (Brosch, 2021 ; Ogunfowora et al, 2023 ), the effects of guilt appeals should be sought immediately after persuasion. Nonetheless, we could not rule out the possibility that delay effects still exist (Brosch, 2021 ) but could not be observed by existing measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of guilt appeals may depend on different time points of measurement after persuasion occurs. Most existing studies measured the effects of guilt appeals immediately after exposure (Peloza et al, 2013 ; Graton et al, 2016 ) because emotional responses are often transient (Brosch, 2021 ; Ogunfowora et al, 2023 ). Nevertheless, recent research suggests that immediate measurement might not capture the desired effects of guilt appeals as people might delay their decisions to adopt the suggested behavior in persuasion (Antonetti et al, 2018 ; Brosch, 2021 ; Kemp, 2023 ).…”
Section: Methodological Moderators Of Guilt Appealsmentioning
confidence: 99%
“…They could use sanitizing or euphemistic language to describe, communicate, or talk about them. People engage in this reframing to realize their goals and to avoid internal/external scrutiny when they perceive positive or desirable outcomes of a behavior that conflicts with their ethical convictions and/or societal norms (Bandura, 1990; Ogunfowora et al, 2023). This could be especially salient for expatriates who, in addition to their own scrutiny, are also under the scrutiny of multiple environments (home, host, and international) possibly in tension with one another, and some of which (e.g., international) might nurture universal ethical norms.…”
Section: A Model Of Expatriate Managerial Misbehaviormentioning
confidence: 99%